2018
DOI: 10.1021/acs.jafc.8b00635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Pressure Treatment on the Muscle Proteome of Hake by Bottom-Up Proteomics

Abstract: A bottom-up proteomics approach was applied for the study of the effects of high-pressure (HP) treatment on the muscle proteome of fish. The performance of the approach was established for a previous HP treatment (150-450 MPa for 2 min) on frozen (up to 5 months at -10 °C) European hake ( Merluccius merluccius). Concerning possible protein biomarkers of quality changes, a significant degradation after applying a pressure ≥430 MPa could be observed for phosphoglycerate mutase-1, enolase, creatine kinase, fructo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Thus, a preservative effect on physicochemical properties of isolated sarcoplasmic 14 and myofibrillar 15 proteins was proved. However, Carrera et al 16 analysed the effects of HPP on muscle proteome by using bottom-up proteomics strategies; as a result, the employment of a high-pressure level ≥ 430 MPa led to a marked denaturation and aggregation of most enzymes. Furthermore, inhibition of Anisakis simplex L3 presence in fresh hake was achieved by Vidacek et al 17 Concerning frozen (5 months at -10 ºC) hake, an inhibitory effect on the formation of deteriorative compounds such as volatile amines, FA and free fatty acids (FFA) was observed by Vázquez et al 18 if previously treated under HPP (150-450 MPa for 2 min).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a preservative effect on physicochemical properties of isolated sarcoplasmic 14 and myofibrillar 15 proteins was proved. However, Carrera et al 16 analysed the effects of HPP on muscle proteome by using bottom-up proteomics strategies; as a result, the employment of a high-pressure level ≥ 430 MPa led to a marked denaturation and aggregation of most enzymes. Furthermore, inhibition of Anisakis simplex L3 presence in fresh hake was achieved by Vidacek et al 17 Concerning frozen (5 months at -10 ºC) hake, an inhibitory effect on the formation of deteriorative compounds such as volatile amines, FA and free fatty acids (FFA) was observed by Vázquez et al 18 if previously treated under HPP (150-450 MPa for 2 min).…”
Section: Introductionmentioning
confidence: 99%
“…1. The dominant protein bands were assigned by comparison with the data reported in relevant researches (Mudalal et al, 2014;Carrera et al, 2018;Wang et al, 2019;Yin et al, 2019;Zhao et al, 2022). The concentrations of separated bands obtained by densitometric analysis are shown in Tables 2 and 3.…”
Section: Sds-page Analysismentioning
confidence: 99%
“…This effect would be of special significance in proteins. Thus, protein denaturation followed by breakdown or damage reactions have shown to be produced as a result of HPP (Pazos et al 2014;Carrera et al 2018), freezing and frozen storage (Sista et al 1997;Sikorski and Kolakowski 2000), and canning (Pérez-Martín et al 1988;García-Arias et al 1994;Mújica-Paz et al 2011). It has been reported that denatured proteins become more reactive and can be damaged easily by interacting with other constituents, especially if a strong processing such as sterilisation is concerned.…”
Section: Changes In Mineral Content In Canned Fish Musclementioning
confidence: 99%